Metabolites from marine microorganisms in cancer, immunity, and inflammation: A critical review - Mario Riera-Romo; Liem Wilson-Savón; Ivones Hernandez-Balmaseda (GarVal Editorial Ltda., 2020)
Context: Marine microorganisms represent a promising source of bioactive molecules for biomedical applications. Increasing scientific literature is describing novel metabolites isolated from marine microbes with attractive pharmacological properties, such as anti-inflammatory, immunomodulatory, and anticancer. Aims: To reveal a background of the main marine microbial-derived products that have been isolated and characterized, including recent examples. The main mechanisms of action of these compounds in different models are also discussed. Methods: This research was structured based on a four phases design. 1) the identification of research questions, 2) selection of relevant studies, 3) filtering of studies based on inclusion and exclusion criteria, and 4) collection and organization of the data. For the web search, were used PubMed, Web of Science, Science Direct and ProQuest. For the selection and classification of the papers was used PRISMA software. Results: A wide variety of marine microbial metabolites with important pharmacological properties have been discovered and characterized so far. The main sources of these compounds are marine actinomycetes, bacilli, fungi from Aspergillus and Penicillium genus, microalgae, and some marine symbiotic bacteria and fungi. Most of these metabolites exhibit cytotoxic, pro-apoptotic, anticancer, anti-inflammatory, and immunomodulatory activities. Complex structural moieties, such as multiple aromatic rings and heteroatoms, seem to be related to these properties. The mechanisms of action of most of these molecules target apoptosis-related proteins, enzymes, transcription factors, DNA binding proteins and some cell surface receptors. Conclusions: The marine environment offers an efficient and attractive way to obtain novel natural products. Marine microorganisms are a prolific source of new molecules and extracts with therapeutic potential in the treatment of chronic inflammatory diseases. They represent and ecofriendly and feasible option to obtain drug candidates with multiple mechanisms of action and important biomedical applications.